Antimicrobial efficacy of composite irrigation solution against dominant pathogens in seawater immersion wound and in vivo wound healing assessment - Wang, Xin; Tan, Jie; Ni, Shenpeng; Zhou, Dengyun; Liu, Baolin; Fu, Qiang (Frontiers in Microbiology, 2023)
Seawater immersion wound is inevitably accompanied by bacterial infection. Effective irrigation is critical for bacterial infection prevention and wound healing. In this study, the antimicrobial efficacy of a designed composite irrigation solution against several dominant pathogens in seawater immersion wounds was evaluated, and in vivo wound healing assessment was conducted in a rat model. According to the time–kill result, the composite irrigation solution exhibits excellent and rapid bactericidal effect against Vibrio alginolyticus and Vibrio parahaemolyticus within 30 s of treatment while eliminating Candida albicans, Pseudomonas aeruginosa, Escherichia coli, and the mixed microbes after 1 h, 2 h, 6 h, and 12 h of treatment, respectively. Significant bacterial count reduction of Staphylococcus aureus was observed after 5 h treatment. In addition to its skin non-irritating attribute, the in vivo wound healing results further demonstrated that the irrigation solution showed high repair efficiency in the skin defect model inoculated with the mixed microbes. The wound healing rate was significantly higher than that of the control and normal saline groups. It could also effectively reduce the number of viable bacteria on the wound surface. The histological staining indicated that the irrigation solution could reduce inflammatory cells and promote collagen fibers and angiogenesis, thereby promoting wound healing. We believed that the designed composite irrigation solution has great potential for application in the treatment of seawater immersion wounds.